2012
DOI: 10.1002/etc.1926
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of fullerene (C60) to sediment‐dwelling invertebrate Chironomus riparius larvae

Abstract: An environmentally realistic method to test fullerene (C(60) ) toxicity to the benthic organism Chironomus riparius was created by allowing suspended fullerenes to settle down, making a layer on top of the sediment. To test the hypothesis that higher food concentrations will reduce toxic responses, two food concentrations were tested (0.5 and 0.8% Urtica sp.) in sediment containing fullerene masses of 0.36 to 0.55 mg/cm(2) using a 10-d chronic test. In the 0.5% food level treatments, there were significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 34 publications
7
64
1
Order By: Relevance
“…On the other hand, acute toxicity tests have reported that fullerenes cause only minor or negligible effects to aquatic organisms (Tervonen et al, 2010;Pakarinen et al, 2011;Fraser et al, 2011;Petersen and Henry, 2012). There is a lack of conclusive data on chronic exposures; some evidence on benthic invertebrates has been reported (Waissi-Leinonen et al, 2012;Pakarinen et al, 2011;Oberholster et al, 2011) and even fewer studies of chronic toxicity to water flea D. magna (Tao et al, 2009). The question of the chronic toxicity of fullerenes to benthic invertebrates covering low concentration ranges has not been solved.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…On the other hand, acute toxicity tests have reported that fullerenes cause only minor or negligible effects to aquatic organisms (Tervonen et al, 2010;Pakarinen et al, 2011;Fraser et al, 2011;Petersen and Henry, 2012). There is a lack of conclusive data on chronic exposures; some evidence on benthic invertebrates has been reported (Waissi-Leinonen et al, 2012;Pakarinen et al, 2011;Oberholster et al, 2011) and even fewer studies of chronic toxicity to water flea D. magna (Tao et al, 2009). The question of the chronic toxicity of fullerenes to benthic invertebrates covering low concentration ranges has not been solved.…”
Section: Introductionmentioning
confidence: 92%
“…dw, particle size <0.5 mm) was added during each treatment just before starting the experiment. The amount of Urtica was chosen to correspond to our previous study; the food level was high enough to be sufficient for this bioassay (Ristola et al, 1999), but did not mark out the potential effect of the fullerenes (Waissi-Leinonen et al, 2012). The dry mass to wet mass ratio of the sediment was determined to be 0.56 to 0.62 and the total organic carbon content (TOC) was 4.51 ± 0.12 g/kg (Multi N/C 2100 Analytic Jena AG Germany).…”
Section: Preparation Of the Test Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the C 60 may also sorb other compounds and the presence of co-contaminants may also play a role in toxic responses (Henry et al, 2007). Recent reports have also highlighted the need for standardizing how C 60 exposure studies are carried out as the preparation of C 60 solutions as well as how the C 60 is spiked into sediment may also alter organism responses Waissi-Leinonem et al, 2012). However, due to the challenges of measuring C 60 in various environmental matrices, this aspect of C 60 exposure studies are still under development (Isaacson et al, 2009).…”
Section: Earthworm Exposure Via Contact and Soil Testsmentioning
confidence: 97%
“…Since C. riparius are sediment-dwelling and deposit-feeding organisms, they have a high probability of bioaccumulating high concentrations of contaminants through sediment ingestion (Oberholster et al, 2011), including contaminants like nanoparticles. Although in the last few years important reports have been released concerning the ecotoxicological effects of NMs to benthic fauna (Oberholster et al, 2011;Waissi-Leinonen et al, 2012;Nair et al, 2013;Bour et al, 2015), the knowledge is still scarce and the topic needs to be addressed further. However, to the best of our knowledge there is no report in the literature about the ecotoxicological effect of NMs bound to contaminants after the treatment of real hazardous organic and inorganic effluents to the C. riparius.…”
Section: Introductionmentioning
confidence: 99%